Persepsi Konsumen Non-Muslim Terhadap Keputusan Pembelian Produk Minuman Halal - Adinugraha, Hendri Hermawan (Li Falah: Journal of Islamic Economics and Business, 2020)
The purpose of this study was to analyze the influence of attitudes, halal labeling, and price perceptions on purchasing decisions for Coca Cola beverage products in Semarang City. This research method uses a quantitative approach, a sample of 100 Non-Muslim consumer respondents using purposive sampling technique and uses multiple linear regression analysis tools. The results of research on perceptions of Non-Muslim consumers towards the decision to purchase halal beverage products indicate that customer attitudes, halal lebelisasi, and price perceptions have a positive effect on the decision to purchase Coca Cola beverage products. The description is that if consumers have a good attitude toward halal drinks, products labeled as halal, and perceptions of prices currently set can be accepted by consumers, the decision to purchase Coca Cola beverage products will increase, and vice versa.